2020
DOI: 10.1097/md.0000000000022357
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Kanglaite injection combined with chemotherapy for colorectal cancer

Abstract: Background: The incidence and mortality of colorectal cancer are high. Chemotherapy is currently the commonly used therapeutic scheme, but there are drug resistance and toxic and side effects. Kanglaite (KLT) injection is a broad-spectrum anticancer drug extracted from Semen Coicis (Yi Yi Ren) , which has been widely used in the treatment of colorectal cancer. Clinical practice shows that KLT injection combined with chemotherapy has certain therapeutic advantages, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Clinically, KLT has synergistic effects with radiotherapy and chemotherapy, it has been used in the adjuvant treatment of various tumors such as lung cancer ( Hailang et al, 2020a ; Li et al, 2020 ), breast Cancer ( Liu S. et al, 2021 ), hepatocellular carcinoma ( Liu et al, 2019 ; Dou et al, 2020 )and colorectal cancer ( Mao et al, 2020 ). The main effects targeted the improvements of clinical efficacy, performance status, KPS score, immune function and the reduction of the side effects of radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, KLT has synergistic effects with radiotherapy and chemotherapy, it has been used in the adjuvant treatment of various tumors such as lung cancer ( Hailang et al, 2020a ; Li et al, 2020 ), breast Cancer ( Liu S. et al, 2021 ), hepatocellular carcinoma ( Liu et al, 2019 ; Dou et al, 2020 )and colorectal cancer ( Mao et al, 2020 ). The main effects targeted the improvements of clinical efficacy, performance status, KPS score, immune function and the reduction of the side effects of radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is a cancer occurring in the colon or rectum, with over 1.9 million new cases and 935,000 deaths estimated in 2020, ranking the third in incidence and the second in mortality (1,2). For patients' treatment, systemic chemotherapy is the mainstay treatment besides surgery and local radiotherapy and has been wildly used in advanced CRC (3).…”
Section: Introductionmentioning
confidence: 99%
“…Coix seed is commonly used in combination with chemotherapy drugs for CRC treatment. Multiple randomized controlled trials indicate that the combination therapy has a higher therapeutic effect and less side effects compared with use of chemotherapy alone [ 12 ]. Several studies in modern medicine have shown that the occurrence and development of CRC are associated with the immune status.…”
Section: Introductionmentioning
confidence: 99%